2006
DOI: 10.1002/app.24047
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cure of phenylethynyl‐terminated AFR‐PEPA‐4 imide oligomer and a model compound

Abstract: The thermal cure reactions of phenylethynyl terminated AFR‐PEPA‐4 oligomer and a model compound N‐phenyl‐[4‐(phenylethynyl) phthalimide] were investigated. The kinetics analysis of the thermal cure of AFR‐PEPA‐4 was determined using DSC, with modified DiBenedetto equation. The activation energy of thermal cure reaction of AFR‐PEPA‐4 oligomer is 34.1 kcal/mol with the kinetic order of one, when the reaction conversion is less than 80%. The activation energy of thermal reaction of N‐phenyl‐[4‐(phenylethynyl) pht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 13 publications
3
40
0
Order By: Relevance
“…The reactive endcapping agents which are commonly used in the polyimide matrix resins include maleic anhydride (MA) [7,8], nadic anhydride (NA) [9,10], and phenylethynylphthalic anhydride (PEPA) [11][12][13][14][15][16][17][18][19], in which MA and NA have been successfully employed in BMI and PMR (In Situ Polymerization of Monomer Reactants) type polyimide matrix resins [3,20,21]. In recent years, it was found that PEPA has some superior features over NA and MA, such as the stronger polymer chain-extending capability than the chain-crosslinking etc [4,[22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The reactive endcapping agents which are commonly used in the polyimide matrix resins include maleic anhydride (MA) [7,8], nadic anhydride (NA) [9,10], and phenylethynylphthalic anhydride (PEPA) [11][12][13][14][15][16][17][18][19], in which MA and NA have been successfully employed in BMI and PMR (In Situ Polymerization of Monomer Reactants) type polyimide matrix resins [3,20,21]. In recent years, it was found that PEPA has some superior features over NA and MA, such as the stronger polymer chain-extending capability than the chain-crosslinking etc [4,[22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of the exothermic curing reaction is at 320 C and the peak reaction rate is reached at 390 C. This is typical for thermally initiated phenylethynyl crosslinking and is similar to results obtained in previous studies on polymers with similar chemistries. 30,31 The total heat of reaction of MHT-R, ÁH is approximately 220 J/g, and hence lower than values for BMI (389 J/ g) 32 and typical aeronautical grade amine cured epoxies (450 J/g). 33 Rheometer tests, both in viscometry mode and oscillation mode, provide the foundation for evaluating the ability to process MHT-R.…”
Section: Resultsmentioning
confidence: 98%
“…To balance the high temperature performance, high hydrolytic resistance and the processing ease of these materials, the exploration of new compositions and new processing methods for polyimides are developing rapidly. Many researchers have demonstrated that termination of various imide oligomers with phenylethynylg roups can lead to dramatic improvements in hydrothermal durability, toughness and processability [3][4][5][6]. The commonly used terminated agent was 4-(phenylethynyl)phthalic anhydride.…”
Section: Discussionmentioning
confidence: 99%